Fundraising zakat lebah madu (Studi kasus pada peternak madu di Kab. Jepara) - Noor Arifin (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The purpose of this study was to analyze the concept of zakat collection for honey beekeepers, honey bee zakat potential, and formulate zakat fundraising strategies for honey bees. This research method is descriptive qualitative with the form of case studies and analysis of data validity using source triangulation. In digging data using observation techniques, independent interviews, and documentation. The results of this study indicate that the honey bee zakat potential is 8.784,3 kg by 665 of boxs, where the average yield of honey reaches 20 Kg in one box / 6 months for each harvest and the strategy for fundraising zakat to be carried out by BAZNAS includes Silaturrahmi, making association, zakah productive distribution method, by BAZNAS account, collaboration with UPZ, and regional mapping, awareness of ZIS, collaboration with institutions, collaboration with leaders, and proactive method.